Improvement in the Output Power of Near-Ultraviolet LEDs of p-GaN Nanorods through SiO2 Nanosphere Mask Lithography with the Dip-Coating Method - Wenkai Yue; Peixian Li; Xiaowei Zhou; Yanli Wang; Jinxing Wu; Junchun Bai (Nanomaterials, 2021)
In this paper, the conditions of the dip-coating method of SiO2 nanospheres are optimized, and a neatly arranged single-layer SiO2 array is obtained. On this basis, a “top-down” inductively coupled plasma (ICP) technique is used to etch the p-GaN layer to prepare a periodic triangular nanopore array. After the etching is completed, the compressive stress in the epitaxial wafer sample is released to a certain extent. Then, die processing is performed on the etched LED epitaxial wafer samples. The LED chip with an etching depth of 150 nm has the highest overall luminous efficiency. Under a 100 mA injection current, the light output power (LOP) of the etched 150 nm sample is 23.61% higher than that of the original unetched sample.